STRUCTURAL MODEL OF DEFORMABLE SOLID DAMAGE - Матченко, Т. І. (Proceedings of National Aviation University (archive), 2021)
The anisotropy of the mechanical characteristics of a solid body, which allow to describe its elastic-deformed state, and the anisotropy of strength characteristics, which allow to describe the process of deformation, are considered. It is proposed to simulate the damage of a solid body using structures with different shapes of cells, which depict systems of axial and diagonal connections that change their characteristics or are removed in the process of impact. Modeling of structures of qualitative nature of damage and their quantitative values ​​for a number of metals is shown.